JFQ volume 18 issue 2 Cover and Back matter (Journal of Financial and Quantitative Analysis, 1983)
Applicants must possess a strong academic research record which also demonstrates a high level of current research involvement. The chaired position, in addition to a competitive salary, includes the resources and support necessary for a continuing high level of research activity and production.